An unexpected zoonosis: pulmonary dirofilaria infection mimicking pulmonary neoplasm - Maxwell, Gordon (Respirol Case Rep, 2019)
Pulmonary dirofilaria infection is a rare condition in Australasia. We describe a case with radiographic findings concerning for pulmonary malignancy, with the unexpected pathological diagnosis of dirofilarial infection.